Complete remission in a rare pelvic angiosarcoma with liposomal doxorubicin: A comprehensive case report and review of literature - Truls Gråberg; Andri Papakonstantinou; Felix Haglund de Flon; Ivan Shabo; Ann Morgell; Christina Linder-Straglitto; Inga-Lena Nilsson; Fredrik Karlsson; Robert Bränström (Rare Tumors)
Angiosarcoma, an aggressive sarcoma subtype originating from lymphatic or vascular endothelial cells, is rare, constituting less than 2% of all soft tissue sarcomas. Predominantly affecting adult and elderly patients, it manifests diversely across various anatomical locations, with cutaneous lesions being the most common, particularly in the head and neck region. Noteworthy for its infiltrative nature, angiosarcoma demonstrates high rates of local recurrence and metastasis, leading to poor overall survival. The diagnosis may be difficult due to nonspecific clinical symptoms, and histological examination is essential in this disease. Treatment typically requires radical surgery, with addition of either chemo- or radiotherapy, or occasionally both, but there is a lack of formal evidence for the order of the modalities employed. Emerging therapies, such as targeted medicines and immunotherapy, show promising results in improving outcomes. This report presents a comprehensive analysis of a rare case of a young male with pelvic angiosarcoma. The patient underwent multiple operations, chemotherapy, and radiation, which highlights the complexities in management and the need for a multidisciplinary approach. Despite challenges, the patient achieved complete remission and is disease-free over 16 years after pelvic exenteration, demonstrating the potential for successful long-term outcomes. The case underscores the importance of personalized, multimodal treatment plans and close collaboration between surgeons and oncologists. Continued research into tailored therapies offers hope for improved prognosis and quality of life for individuals facing this uncommon sarcoma.